ALAT PENGAMAN KANDANG BERBASIS MIKROKONTROLER ARDUINO UNO - Wire Bagye; Tsurayya Azizah; Muhammad Fauzi Zulkarnaen (Jurnal Informatika dan Rekayasa Elektronik, 2018)
The occurrence of theft is often in the chicken coop, the impact of this theft is that farmers experience material losses so that the farmer is no longer raising chickens. security system applied by the owner of the cage by way of patrolling at night. even though the patrol has been carried out, there are still frequent thefts because thieves are lurking in patrol activities, theft occurs when the owner of the house is unaware. a tool that is able to provide information that there are people who enter the cage to owners who work indefinitely. The analytical method that will be used in this study is the SWOT method (Strength, Weakness, Opportunity, Threat). This method is used by researchers to collect information and conduct needs analysis. To solve the problem, a safety device with Arduino was built, a pir sensor, an 800L SIM. The enclosure safety device works to detect human body heat with the PIR Motion sensor, if there is a human crossing the Arduino sensor area it gives a signal to the 800L SIM to send a message to the cellphone owner's cellphone. The message informs that there are humans in the chicken coop. results of the test showed that 100% of case can be sent by Alat Pengaman Kandang Ayam Berbasis Mikrokontroler Arduino, namely from 20 attempts to produce 20 messages to cellphone owners with vulnerable time of 3 seconds